Revisiting Malaysian Cinema : From National Supports to State Intervention - Lee, Yow Chong (Universiti Malaysia Sarawak (UNIMAS), 2014)
This paper is tailored to look into the development of Malaysian cinema since the incipient of studio system, based in Singapore, and its later shift to Malaysia in another phase, hitherto identified as the independent era. This paper proposes that the collapse of studio system in the mid 1970s demonstrated the logic of capitalist system as it never tolerate the industry which no longer generates much money, on one hand; and it also marked the watershed for the intensified intervention of the state in Malaysian film industry, both in financial supports and its cascading effects such as rules and regulations and censorship impose on the film industry players, on the other. Apart from this, the author will also shed light on several prominent figures and institutions for whom (which) have substantially shaped the film industry existing today, just to name a few, the multitalented and renowned filmmaker, P. Ramlee; the controversial filmmaker, Amir Muhammad and his films, as well as FINAS and the Censorship Board. In other words, this paper will address, not only the interplay of capitalist system and the state intervention, but also the effects of such interaction on Malaysian cinema.